IMPLEMENTASI DAN SOSIALISASI PENGGUNAAN QRIS BAGI UMKM DESA RANCAGONG RW 07 KABUPATEN TANGERANG - Lianda, Tara Anabel Christy; Austin, Noven; Putri, Nazwa; Setiawan, Budi (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2026)
Digital transformation in the payment system has become an urgent need for Micro, Small, and Medium Enterprises (MSMEs) to enhance competitiveness and transaction efficiency. One relevant innovation is the implementation of QRIS (Quick Response Code Indonesian Standard) as an integrated digital payment system. However, low digital literacy and limited access to information have prevented many MSMEs from utilizing QRIS optimally. This Community Service Program (PKM) aimed to improve understanding and provide assistance to MSMEs regarding the implementation of QRIS. The methods used included socialization and direct mentoring. The socialization aimed to provide knowledge about the benefits and mechanisms of QRIS, while the mentoring focused on the registration, activation, and usage processes in daily transactions. The activity was conducted in Rancagong Village, RW 07, involving 10 MSME participants. However, only 4 MSMEs already had QRIS, and 4 another were willing and successfully registered due to sufficient device readiness and willingness to adapt. Meanwhile, the remaining 2 MSMEs were unable to register due to limited access to adequate smartphones and concerns about the security of digital systems. The results of the program indicated that socialization and mentoring had a positive impact on improving MSMEs' digital literacy, although further efforts are needed to overcome technological barriers and expand QRIS adoption.